IDEAS ABOUT THE DEVELOPING ENVIRONMENT FOR CHILDREN AS A SUBJECT OF THEORETICAL ANALYSIS - Matiushynets, Yana (Educological discourse, 2018)
The article highlights the historical and pedagogical analysis of the views of Ukrainian pedagogues of the late 19th - early 20th century on the creation and functioning of a developing environment for children. The author considers the main approaches to the organization of the education, upbringing and development of preschool and children of primary school age (child-centeredness, nature-type, teaching in the environment) and the features of creating the developing environment at different time intervals (1899-1918). The goals, the tasks of the functioning of various institutions for children in accordance with the social, economic, political and cultural changes in the territory of Ukraine at the end of the 19th and the beginning of the 20th century (the need for moral and physical education of the individual, the observance of the national character of education, the individual approach) have been clarified. The author in article disclose the contribution Ukrainian pedagogues to the development of the problem of the functioning of the developing environment for children: the preservation of the life and health of children, the provision of physical and moral education of the individual; ensuring the preparation of the child for school, the education of moral qualities, discipline; ensuring native language environment, preparation of children for life; creation of an environment for children on the principles of individuality, nationality, revealing the creative forces of the child, aesthetic development mental and physical development of the individual.